Methoxyflurane (Penthrox®)—a case series of use in the prehospital setting. (2nd February 2019) - Forrest, Mark; Porter, Keith; van der Velde, Jason
Abstract : Methoxyflurane (Penthrox ® ) is a fluorinated hydrocarbon, which when first used in general anaesthesia was noted to have strong analgesic properties in subanaesthetic dosage. More than 5 million doses have been sold for use in Australia since 1978 and have been found to have an excellent safety profile. After rigorous review by the Medicines and Healthcare Regulatory Agency, methoxyflurane was granted a product licence in 2015 in the UK and Europe for the relief of pain in patients with moderate-to-severe trauma. This paper presents the first reported case series of patients treated with methoxyflurane in the UK and Ireland in the prehospital environment. The results show a statistically significant improvement in patient pain scores at 1, 2 and 5 minutes following administration of methoxyflurane. With its use increasing in prehospital care and emergency departments, methoxyflurane is recognised as a useful adjunct to the choice of analgesia for trauma patients with moderate-to-severe pain.